Analysis the Supreme Court Decision and the Constitutional Court Decision Regarding the Age Limit for Regional Head Candidates - Bobby Thyas Erlangga; Karlinae D. Bangas; Ivans Januardy (Dinasti Research, 2025)
This study purpose to analyze a decision made by Constitutional Court Number 70/PUU-XXII/2024 and the decision made by Supreme Court Number 23 P/HUM/2024 Relate to the age limit for a region head candidates. In the context of the hierarchy of norms in Indonesia, the dualism of authority to examine laws and regulations by the Supreme Court and the Constitutional Court often leads to conflicts of substance. The study used in this research is a type of normative juridical research method by approaching the law and case studies to assess whether there is a conflict of norms and legal vacuum. The results show that there are differences in interpretation between the two institutions regarding the minimum age of candidates for regional heads, which has an impact on legal uncertainty. To overcome this problem, it is necessary to reform the mechanism for testing statutory instruments, including the proposal for a single test at the Constitutional Court or the addition of norms to the Supreme Court Law regarding the validity of decisions in the event of changes in statutory norms. Research with the title analysis of this is expected to be a contribution to the optimization of the legal system in Indonesia.